Ink-Jet Printed Cu/CuxO/Ag ReRAM Memory Devices Fabricated on Flexible Substrate. Issue 1692 (14th October 2014) - Zou, Simin; Hamilton, Michael C.
ABSTRACT: Recently, flexible electronics is attracting growing attention due to its various properties such as lightness and flexibility, which cannot be replaced by rigid electronics. In this study, we investigate flexible ink-jet printed Cu/CuxO/Ag capacitor-like structure that exhibits bipolar resistive switching behavior under direct current voltage sweeps. A vaccum-free and low temperature process is used to fabricate this ReRAM memory device, which allows straightforward fabrication and a structure for characterization of the possible use of CuxO as an insulating layer in these devices. Our device displays a resistive switching ratio greater than 30 between the high resistance and low resistance state at room temperature. The devices exhibit metallic behavior in the low resistance state and a semiconductor behavior is found in the initial and high resistance states as observed in temperature dependent resistance measurements. The resistive switching mechanism of the fabricated structures is explained by the formation and rupture of conductive filament paths.